Physics of the Future: The inventions that will Transform our Lives (Global Business Management Review (GBMR), 2022)
Through his recently published book, Physics of the future: The inventions that will transform our lives, Michio Kaku unfolds an amazing virtual world in front of us through the imaginary journey into the technology dominated century. The book transpires through 300 interviews Kaku did with world renowned scientists in the field of physics and related areas including nanotechnology, medicine, computers and space. Being a quantum physicist himself, Kaku had first-hand information of some of the emerging technology inventions from the most sophisticated research labs around the world. In addition to writing, researching and teaching, Kaku is one of the most sought after hosts in the Sci-Fi Science channel. Through a researcher’s keen eyes Kaku narrates some of the limitless possibilities of technology. Few of such predicted inventions are X-ray visions, space elevators and atom sized chips. He talks about micro machines which can perform complex surgeries. Those who are not keen on technology may find the book a bit dry to sustain until the last chapter. One of the negatives of the book for a layman reader is that the language used is not tuned for a science fiction. Most of the places Kaku depends on mathematics and complex algorithms to explain a phenomenon. While explaining on advance medical technology, Kaku brings about many an invention like pocket size MRI scanners, self-screening toilet sets, clothes which can act as embryonic etc. For Kaku, the future will fully be built on internet where with the blink of an eye one could log in and off. He says an extinct world can be re produced with the help of technology. May be T-rex and dinosaurs come alive one day and even Neanderthals is a possible options in Kaku’s list.